2018
DOI: 10.4067/s0718-95162018005000601
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous nitric oxide on cadmium toxicity and antioxidative system in perennial ryegrass

Abstract: The effects of sodium nitroprusside (SNP, a donor of NO) on cadmium (Cd) toxicity in ryegrass seedlings (Lolium perenne L.) were studied. 100 and 150 μM Cd stress had a detrimental effect on ryegrass seedlings. Exposure of 100 and 150 μM Cd inhibited plant growth, decreased chlorophyll concentration, and reduced the absorption of Fe, Cu and Zn. Excess Cd also altered the activities of antioxidant enzymes, and increased the accumulation of reactive oxygen species (ROS). Exogenous NO alleviated Cd toxicity of ry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 21 publications
4
12
0
Order By: Relevance
“…In the current experiment, Cd toxicity markedly reduced the growth attributes of cowpea plants, including shoot length, shoot biomass and leaf area. These results are in conformity with the previous findings on different plant species (Jhanji et al, 2012;Perveen et al, 2016;Sun et al, 2016;Chen et al, 2018). Nonetheless, seed priming with Pro or GB, especially 50mM Pro, improved all measured growth parameters under Cd stress.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current experiment, Cd toxicity markedly reduced the growth attributes of cowpea plants, including shoot length, shoot biomass and leaf area. These results are in conformity with the previous findings on different plant species (Jhanji et al, 2012;Perveen et al, 2016;Sun et al, 2016;Chen et al, 2018). Nonetheless, seed priming with Pro or GB, especially 50mM Pro, improved all measured growth parameters under Cd stress.…”
Section: Discussionsupporting
confidence: 93%
“…MDA, an end product of membrane lipid peroxidation is a proper marker for oxidative stress by heavy metal toxicity. In the current experiment, an elevated level of MDA in cowpea leaves was observed in Cd treated plants, which is conformity with the other findings (Shamsi et al, 2008;Ahmad et al, 2016;Chen et al, 2018). However, in this study, seed priming with Pro or GB significantly reduced the MDA level under Cd toxicity.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, other bioactive compounds such as melatonin reversed the oxidative stress in tomato plants grown under high temperature (Ahammed et al ). NO may also increase the activities of antioxidant enzymes in plants subjected to stress regimes (Kovacik et al , Chen et al ). This study also showed that SNP augmented the antioxidant enzyme activities in the leaves to scavenge ROS induced by Cd stress.…”
Section: Discussionmentioning
confidence: 99%
“…As stated earlier, metals induce ROS accumulation in plant cells, often resulting in a marked reduction of the photosynthetic efficiency. However, according to multiple records, the signaling molecule NO is able to counteract the negative effects of metals on the redox state of the cell, helping towards a better photosynthetic yield (Jhanji et al , Khairy et al , Chen et al ). The mechanisms by which NO is able to protect the photosynthetic machinery, as well as its metabolic chains, are illustrated in Fig.…”
Section: Regulation Of the Photosynthetic Machinery By No Under Metalmentioning
confidence: 99%